Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm not sure how to go about proving this theorem:

Let $f:\mathbb{R}^m \longrightarrow \mathbb{R}^m,f\in C^1(\mathbb{R}^m)$ such that:

$\|f'(x)(v)\|=\|v\|,\forall v\in \mathbb{R}^m,\forall x \in \mathbb{R}^m$

Prove that $\|f(x)-f(y)\|=\|x-y\|,\forall x,y\in \mathbb{R}^m$.

Any hints would be appreciated.

By the Theorem of the Mean Value Inequality, we have $\|f(x)-f(y)\|\le\|x-y\|,\forall x,y\in \mathbb{R}^m$.

share|cite|improve this question
up vote 0 down vote accepted

Let $\alpha(t)=x+t\frac{(y-x)}{\|y-x\|}$ with $t\in[0,\|y-x\|]$ and $x,y\in\mathbb{R}^{n}$. So $\alpha$ is parametrized byt arc length, therefore, $\|(f\circ\alpha)'(t)\|=\|f'(\alpha(t))\alpha'(t)\|=\|\alpha'(t)\|=1$, hence the curve $(f\circ\alpha)(t)$ is parametrized by arc length. By using these facts and the definition of arc length, can you finish?

share|cite|improve this answer
Thanks Tomás for your solution, but I have problems with $(f\circ\alpha)(1)=f(x+\frac{y-x}{||y-x||})$ and definition $l(f\circ\alpha)[0,1]=\sum_{i=1}^{n}||(f\circ \alpha)(t_i)-(f\circ \alpha)(t_{i-1}))||$ – felipeuni Oct 23 '12 at 1:17
Sorry, it is not $[0,1]$, it is $[0,\|y-x\|]$. I will edit it – Tomás Oct 23 '12 at 11:37

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.